Clinical Characteristics of Somatic Mutations in Chinese Patients With Aldosterone-Producing Adenoma. Issue 3 (March 2015) - Zheng, Fang-Fang; Zhu, Li-Min; Nie, Ai-Fang; Li, Xiao-Ying; Lin, Jing-Rong; Zhang, Ke; Chen, Jing; Zhou, Wen-Long; Shen, Zhou-Jun; Zhu, Yi-Chun; Wang, Ji-Guang; Zhu, Ding-Liang; et al.
<x xml:space="preserve">Abstract</x> Recent studies have shown that somatic mutations in the KCNJ5, ATP1A1, ATP2B3, and CACNA1D genes are associated with the pathogenesis of aldosterone-producing adenoma. Clinical profile and biochemical characteristics of the mutations in Chinese patients with aldosterone-producing adenoma remain unclear. In this study, we performed DNA sequencing in 168 Chinese patients with aldosterone-producing adenoma and found 129 somatic mutations in KCNJ5, 4 in ATP1A1, 1 in ATP2B3, and 1 in CACNA1D. KCNJ5 mutations were more prevalent in female patients and were associated with larger adenomas, higher aldosterone excretion, and lower minimal serum K+ concentration. More interestingly, we identified a novel somatic KCNJ5 mutation (c.445-446insGAA, p.T148-T149insR) that could enhance CYP11B2 mRNA upregulation and aldosterone release. This mutation could also cause membrane depolarization and intercellular Ca2+ increase. In conclusion, somatic KCNJ5 mutations are conspicuously more popular than mutations of other genes in aldosterone-producing adenomas of Chinese patients. The T148-T149insR mutation in KCNJ5 may influence K+ channel selectivity and autonomous aldosterone production.